2022
DOI: 10.35229/jaes.1160228
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Molecular Response to Heavy Metal Stress in Plants

Abstract: Artan antropojenik etki ve endüstrileşme ile birlikte doğal ekosistemlerin dengeleri bozulmakta ve birçok canlının tolere edilebileceği düzeylerin üzerinde ağır metal birikmektedir. Sesil organizmalar olan bitkiler ağır metal kirliliğine maruz kaldıklarında verimliliğin azalması ve ürünlerde kalite kaybının yaşanması gibi ciddi sonuçlarla karşı karşıya kalınmaktadır. Bu ağır metallerden bakır (Cu), çinko (Zn), kobalt (Co), mangan (Mn), molibden (Mo) ve nikel düşük düzeylerde bitkiler için gerekli olduğu halde … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The reduction in RL was 43% in RK-106 and 59% in Toros İri Yaprak. Yıldırım et al (2019) stated that root growth in rockets was suppressed under Cd and Pb stress and that oxidative damage in the plant under heavy metal stress adversely affected plant metabolism (Sevgi & Leblebici, 2022), and consequently, plant growth and suppression in root development were two of the most important symptoms of heavy metal stress. They also found that Cd stress caused a decrease in Mg and Fe content.…”
Section: Rocketmentioning
confidence: 99%
“…The reduction in RL was 43% in RK-106 and 59% in Toros İri Yaprak. Yıldırım et al (2019) stated that root growth in rockets was suppressed under Cd and Pb stress and that oxidative damage in the plant under heavy metal stress adversely affected plant metabolism (Sevgi & Leblebici, 2022), and consequently, plant growth and suppression in root development were two of the most important symptoms of heavy metal stress. They also found that Cd stress caused a decrease in Mg and Fe content.…”
Section: Rocketmentioning
confidence: 99%